PENDIDIKAN ISLAM BERORIENTASI MASA DEPAN; KONSEP PENDIDIKAN ULUL ALBAB PERSPEKTIF IMAM SUPRAYOGO - Zamroni, Zamroni (JURNAL AT-TURAS, 2014)
In this technological era, Islamic education is a basic requirement. Therefore, the presence of technology has succeeded in eroding the values of intellectual and human spiritual in today’s situation. By this, the need of Islamic education is functioned to balance the rigors of technology influences in education. Conceptually, Islamic education is not only a kind form of intelligence but also educate the spiritual aspect, thus forming a complete human morality. Education which accommodates the aspect of intelligence development together with spiritual will deliver human into a good future that will be called as “personal ulul albab”. This concept is such what trying initiated by Imam Suprayogo in the teaching process at UIN Maulana Malik Ibrahim Malang. According to him, the elaboration of the physical and spiritual needs is important in shaping the human personality so that he/she could behave well in life. Philosophically education Ulu al-Albab see that man called ulu al-albab is a human figure that puts the dhzikir, thought and charity as the first human priority. By this concept, it is expected to be a form of intelligent personal intellectual (IQ), emotionally intelligent (EQ) and spiritually intelligent (SQ).